Perbedaan Kemampuan Sosialisasi antara Siswa yang Mengikuti dan yang Tidak Mengikuti Kegiatan Ekstrakurikuler - Titiek Syamsiah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
The Difference of Socialization Capability between Pupils Attending and Pupils Not Attending Extracurricular Activities. This study was designed to investigate the difference in socialization capability between pupils attending and pupils not attending extracurricular activities. There were 70 elementary school pupils selected randomly to be the sample, consisted of 35 pupils attending and 35 pupils not attending extracurricular activities. The data were collected by check lists and interviews, and were then analyzed statistically by t-test. The result revealed that the socialization capability of pupils attending extracurricular activities was better than those not attending extracurricular activities.